Analisis Strategi Pemasaran (Studi Kasus di Omaku Pusat Jajanan Tradisional, Kecamatan Kepanjenkidul, Kota Blitar) - M. Halim Fawazi; Puji Rahayu (Translitera : Jurnal Kajian Komunikasi dan Studi Media, 2021)
Omaku Center for Traditional Snacks is one of the home industries where the main product is traditional snacks such as wet snacks in general. Starting from two peddlers, Mrs. Rusli Prijanto, started trying to open a wet snack business. Initially it was still located on Jl. Blitar 100 orchids. One of the differences of these products is the recipe for traditional wet snacks made which is distinctive and guaranteed and stable. The purpose of this study is to analyze and determine marketing strategies that can be applied to the Omaku Traditional Snack Center. The analysis used was the SWOT approach and descriptive analysis used a qualitative research approach to respondents who were given a questionnaire in which the respondents were selected by purposive sampling technique. For this reason, it is necessary to recognize the company's condition and internal and external factors that have an influence on the marketing strategy. For data collection, it was done by interview, questionnaire and direct observation. In addition, data is collected through supporting data obtained from books, previous research and related sources. The data obtained is based on the data that has been collected, then an analysis is carried out using a SWOT approach in order to find out which marketing strategies can be used based on the strengths, weaknesses, opportunities, and threats of the company. The results showed that the company's grand strategy matrix is ​​included in quadrant I, where the implementation of aggressive or growth strategies is a very favorable condition for the company. The company has the power to be able to where, the company has the power so that it can use the existing opportunities.